Economic evaluation of Tambatinga larviculture (Colossoma macropomum x Piaractus brachypomus) at different stocking densities in a biofloc system (Research, Society and Development, 2021)
The objective of this study was to carry out an economic evaluation of Tambatinga larviculture in three stocking densities (10, 20 and 30 post-larvae / liter) submitted to the biofloc system (BFT) and clear water (AC) using the data zootechnics collected during a 12-day experimental period. Larviculture was designed for the city of Cuiabá-Mato Grosso. The Effective Operating Cost, Total Operating Cost and Total Production Cost (CT) were measured, and the cost-benefit analysis of the BFT and AC systems was performed using the financial-productive indicator (Ifp) (g / R $). The CTs (R $ / liter) of treatments with BFT were R $ 0.0843 (10 post-larvae / liter), R $ 0.134 (20 post-larvae / liter), R $ 0.1837 (30 post-larvae) / liter), these values ​​being higher than the CTs found in CA of R $ 0.0588, R $ 0.1088, R $ 0.1589, respectively. Ifps, of densities 10, 20 and 30 in BFT, in this order, were 0.287g, 0.1392g and 0.0651g for each R $ 1.00 of CT. In AC, the Ifps were 0.0639g / R $ 1.00, 0.0789g / R $ 1.00 and 0.1052g / R $ 1.00, as the density increased. Through Ifp, it was possible to assess that even with a higher TC, the use of BFT systems, with a density of 10 and 20 post-larvae / liter, allows greater gain of final biomass for each real allocated in the activity.